THE INFLUENCE OF PARENTING PATTERNS ON STUDENTS' LEARNING OUTCOMES OF GRADE II UPT SPF SDN TIDUNG MAKASSAR - Hamsiah, Andi (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to (1) Identify and analyze the influence of parenting patterns on the learning achievement of class II students at UPT SPF SD Negeri Tidung, Makassar City (2) Identify and analyze the influence of social interaction on the learning achievement of class II students at SD Negeri Tidung, Makassar City (3) Determine and analyze the influence of parenting patterns on learning outcomes of class II at UPT SPF SD Negeri Tidung, Makassar City. This study uses a quantitative approach with a sample of 30 students—data collection techniques include questionnaire techniques and documentation. Data analysis techniques include descriptive analysis, multiple linear regression analysis, t-test, and f-test. The results of the study indicate that the parenting pattern used by parents at UPT SPF SD Negeri Tidung, Makassar City, namely democratic parenting, has a positive effect on student learning outcomes.